Critical path method (CPM) for scheduling a type 36 residential house construction at Grand Permata Hijau housing, Samarinda city - Khoirur Rosidin; Maulana Hamdan Rifa’i; Deddy Pramana Zulkarnain; Surahman Surahman; Tandi Kadang (Enrichment : Journal of Management, 2026)
Small-scale residential construction projects often experience delays due to weak schedule control and unstructured scheduling. This study aims to apply the Critical Path Method (CPM) to schedule the construction project of a Type 36 residential house at Grand Permata Hijau Housing, Samarinda City, to identify the critical path and determine the optimal completion duration. This research used a quantitative descriptive approach with a case study method. Project data, including the Cost Budget Plan (RAB) and initial schedule, were analyzed by constructing an Activity on Node (AON) network diagram, followed by forward pass and backward pass calculations. The CPM result indicates a potential reduction in project duration compared with the initial 120-calendar-day target. The resulting critical path consists of nine activities, including Preparation Work (A), Foundation Work (C), Concrete Work (D), Wall Masonry Work (E), Roofing Work (H), Ceiling Work (I), Wood & Frame Work (J), Painting Work (L), and Handover (O). This study proves that the CPM method is effective in optimizing scheduling time and can serve as a reference for time control in small-scale residential construction projects at the local level